Phase transitions of α‐quartz at elevated temperatures under dynamic compression using a membrane‐driven diamond anvil cell: Clues to impact cratering?. (6th April 2018) - Carl, Eva‐Regine; Liermann, Hanns‐Peter; Ehm, Lars; Danilewsky, Andreas; Kenkmann, Thomas
Abstract: Coesite and stishovite are high‐pressure silica polymorphs known to have been formed at several terrestrial impact structures. They have been used to assess pressure and temperature conditions that deviate from equilibrium formation conditions. Here we investigate the effects of nonhydrostatic, dynamic stresses on the formation of high‐pressure polymorphs and the amorphization of α‐quartz at elevated temperatures. The obtained disequilibrium states are compared with those predicted by phase diagrams derived from static experiments under equilibrium conditions. We analyzed phase transformations starting with α‐quartz in situ under dynamic loading utilizing a membrane‐driven diamond anvil cell. Using synchrotron powder X‐ray diffraction, the phase transitions of SiO2 are identified up to 77.2 GPa and temperatures of 1160 K at compression rates ranging between 0.10 and 0.37 GPa s −1 . Coesite starts forming above 760 K in the pressure range between 2 and 11 GPa. At 1000 K, coesite starts to transform to stishovite. This phase transition is not completed at 1160 K in the same pressure range. Therefore, the temperature initiates the phase transition from α‐quartz to coesite, and the transition from coesite to stishovite. Below 1000 K and during compression, α‐quartz becomes amorphous and partially converts to stishovite. This phase transition occurs between 25 and 35 GPa. Above 1000 K, no amorphization of α‐quartz is observed. High temperature experiments reveal the strong thermal dependence of the formation of coesite and stishovite under nonhydrostatic and disequilibrium conditions.